Pengaruh Model Pembelajaran Collaborative Learning Terhadap Kemampuan Berpikir Reflektif Siswa SMP Negeri 1 Hiliduho - Mendrofa, Ignasius; Telaumbanua, Yakin Niat; Mendrofa, Ratna Natalia; Mendrofa, Netti Kariani (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is based on the results of a preliminary study conducted by researchers at SMP Negeri 1 Hiliduho. The problems identified were: (1) insufficient variety of classroom learning models and (2) students' lack of reflective thinking skills in solving mathematics problems. The purpose of this study was to determine the effect of the Collaborative Learning model on students' reflective thinking skills at SMP Negeri 1 Hiliduho. This quantitative study used a quasi-experimental method with a pretest-posttest control group design. The population was eighth-grade students, and the sample consisted of two classes: VIII-A as the experimental class and VIII-C as the control class. The instrument used was a descriptive test of reflective thinking skills. The research results obtained based on one-way hypothesis testing yielded a calculated t value of 4,628 and a t value of 2.024. Since t value > t value, or 4,628 > 2.024, H0 is rejected and Ha is accepted, meaning